Non-diabetic elderly populations: the MHR as a protective factor against bone abnormalities - Li, Xiang; Yan, Manli; Ji, Jiali; Ma, Zhuohao (Frontiers in Endocrinology, 2024)
Objective In China, osteoporosis has become a major health concern among elderly population, imposing significant burden on the country's social and economic systems. The monocyte to high-density lipoprotein ratio (MHR) has been currently recommended as a novel marker of inflammation and oxidative stress associated with osteoporosis in type 2 diabetes mellitus (T2DM). However, its reliability in non-diabetic elderly populations remains unclear. The present study was to evaluate the association between MHR and osteoporosis in a non-diabetic elderly population. Methods The clinical data of 240 non-diabetic elderly subjects (115 in the osteoporosis group and 125 in the normal bone group) were retrospectively analysed and all statistical analyses were performed by using SPSS 26.0. Results Differences in age, neutrophils, lymphocytes, monocytes, MHR, uric acid, creatinine, triglycerides ,and high-density lipoprotein cholesterol were found to be statistically significant between the two groups. A binary logistic regression model was conducted by including age, MHR, UA and Cr as variables. The results showed that age was an independent risk factor and MHR was an independent protective factor for bone abnormality in the non-diabetic elderly population. The ROC analysis showed that the area under the curve for the predictive effect of MHR, age and their combined test on osteoporosis in non-diabetic elderly populations was 0.623, 0.728 and 0.761, respectively; the correlation analysis showed that MHR was positively correlated with lumbar and hip BMD, and negatively associated with femoral neck stress ratio, femoral intertrochanteric stress ratio, and femoral stem stress ratio, showing statistically significant differences (P<0.05). Conclusion For the non-diabetic elderly population: the MHR is a protective factor against bone abnormalities and was significantly higher in the normal bone group than in the abnormal bone group.